[RETRACTED] Job Insecurity and Employee’s Performance: Examining through the Perspective of Psychological Strains and Leverages - Shahi, Rajesh; Gautam, Niraj (The Lumbini Journal of Business and Economics, 2023)
RETRACTION NOTICE: Due to a high level of overlap with the article listed below, this article was retracted on 3rd July 2023. Darvishmotevali, M., Arasli, H. and Kilic, H. (2017), "Effect of job insecurity on frontline employee’s performance: Looking through the lens of psychological strains and leverages", International Journal of Contemporary Hospitality Management, Vol. 29 No. 6, pp. 1724-1744. https://doi.org/10.1108/IJCHM-12-2015-0683